Preparation method of latex agglomeration type ion chromatographic column

By synthesizing latex spheres with gradient structures and quaternary amination and agglomeration treatment, latex agglomeration type anionic chromatography column fillers with strong hydrophilicity and good chromatographic stability under strong alkali environments were prepared, which solved the problem of insufficient hydrophilicity when used in strong alkali environments in the prior art.

CN119701902APending Publication Date: 2025-03-28ANHUI NOPU NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411633539.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing latex agglomerated anion chromatographic fillers have problems of insufficient hydrophilicity and poor structural stability when used in strong alkali environments.

Method used

By synthesizing vinylbenzyl chloride-divinylphenyl-allyl glycidyl ether monodispersed non-porous latex spheres with gradient structures, and quaternary amination reaction is performed to obtain quaternary amination latex spheres containing β-hydroxyl groups, and finally electrostatic agglomeration with the sulfonated spheres to prepare a latex agglomeration anion column filler.

Benefits of technology

The hydrophilic latex agglomerated anion chromatography column filler used in a strong alkali environment has strong hydrophilicity and good chromatographic stability. The seven anions are tested to have moderate broadening and fast peaking time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of a latex agglomeration type anion chromatographic column filler. The prepared filler is used for filling a chromatographic column. The method comprises the following steps: firstly, synthesizing vinyl benzyl chloride-divinylbenzene-allyl glycidyl ether monodisperse nonporous latex spheres with gradient structures from core to shell, and carrying out quaternization reaction on the vinyl benzyl chloride-divinylbenzene-allyl glycidyl ether monodisperse nonporous latex spheres to obtain modified quaternized latex spheres containing beta-hydroxyl; sulfonating the polystyrene-divinyl benzene porous ball to obtain a sulfonated base ball; finally, the quaternized latex balls and the sulfonated balls are agglomerated through electrostatic interaction, and the hydrophilic latex agglomerated anion chromatographic column filler is obtained. The prepared hydrophilic latex agglomerated anion chromatographic column filler has strong hydrophilicity and good chromatographic stability, and is moderate in broadening of seven anions and short in peak appearance time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ion chromatography column, in particular to a preparation method of a latex agglomerated ion chromatography column. Background Art

[0002] The core component of ion chromatography separation is the chromatographic column, and the performance of the chromatographic column depends on the characteristics of the filler in the column. Although domestic and foreign manufacturers have developed various types of chromatographic column fillers, relying on modification technologies including but not limited to hyperbranching and surface grafting, latex agglomeration is still the main product and key research and development direction in the current ion chromatography field due to its ultra-high mass transfer efficiency.

[0003] The general preparation method of traditional anion chromatography fillers is: first chloromethylate polystyrene-divinylbenzene microspheres, and then quaternize the introduced chloromethyl side groups (-CH2Cl) with tertiary amines (R1R2R3N) to obtain the fillers. The preparation method of the usual latex agglomerated anion chromatography fillers mainly includes two parts: one is the preparation and modification of the base ball to make it positively charged; the other is the preparation and modification of the latex ball to make it quaternized. At present, the preparation of the base ball adopts the most widely used styrene-divinylbenzene system, and the modification is sulfonation to make it positively charged. The preparation of conventional latex balls is generally made by the reaction of vinylbenzyl chloride (VBC) and divinylbenzene (DVB), or by the reaction of glycidyl methacrylate (GMA) and divinylbenzene (DVB). Then react with a tertiary amination reagent to generate quaternized latex balls, and finally react with the sulfonated base balls to make latex agglomerated anion chromatography fillers through electrostatic adsorption.

[0004] However, the latex agglomerated anion chromatographic fillers prepared above each have their own limitations: the former is too hydrophobic, and due to the hydrophobic effect, it is difficult to elute multivalent ions or strongly retained ions, and the peak shape is poor; and although the latter has excellent hydrophilic properties and the β-hydroxyl group is introduced during the quaternization process to improve the peak shape, it cannot be used in a strong alkaline environment due to the presence of an ester group in the structure. Summary of the invention

[0005] In order to solve the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a latex agglomerated ion chromatography column. The ion chromatography column prepared by the method can be used in a strong alkaline environment and has good hydrophilicity.

[0006] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a latex agglomerated ion chromatography column, comprising the following steps:

[0007] S1, synthetic latex ball;

[0008] S2, quaternizing the synthesized latex balls;

[0009] S3, agglomerating the quaternized latex balls with the sulfonated balls to obtain a latex agglomerated ion chromatography filler;

[0010] S4, packing the obtained latex agglomerated ion chromatography filler into a column and testing it;

[0011] Wherein, in step S1, the step of synthesizing latex balls is:

[0012] S11, adding vinylbenzyl chloride monomer, emulsifier and initiator into a container, and forming latex balls with a core structure by emulsion polymerization;

[0013] S12, adding a cross-linking agent into the container to react, so that the nuclear structure of the latex ball is amplified;

[0014] S13, adding pre-emulsified allyl glycidyl ether and an initiator into a container to obtain monodisperse nonporous latex spheres having a core-shell structure of vinylbenzyl chloride-divinylbenzene-allyl glycidyl ether.

[0015] Optionally, in step S3, the step of obtaining the latex agglomerated ion chromatography filler is:

[0016] S31, taking styrene-divinylbenzene porous microspheres and sulfonating them to make the styrene-divinylbenzene porous microspheres positively charged to obtain sulfonated microspheres;

[0017] S32, electrostatically agglomerating the quaternized latex balls with the sulfonated balls to obtain a latex agglomerated ion chromatography column filler.

[0018] Optionally, in step S11, the reaction temperature of the emulsion polymerization is 50-90° C., and the reaction time is 0.5-4 hours;

[0019] The initiator is one or more of azobisisobutylamidine hydrochloride, potassium persulfate, and ammonium persulfate, and the weight percentage of the initiator is 0.05 wt% to 2 wt%;

[0020] The emulsifier is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium dihexyl sulfosuccinate, and the weight percentage of the emulsifier is 1wt% to 3wt%.

[0021] Optionally, in step S12, the cross-linking agent is divinylbenzene, and the weight percentage of the cross-linking agent is 2.5wt%~12.5wt%;

[0022] The reaction time of the cross-linking agent is 0.5 to 4 hours.

[0023] Optionally, in step S13, the weight percentage of the allyl glycidyl ether is 60wt%~80wt%.

[0024] Optionally, in step S2, when the latex balls are quaternized, a dispersant is added to the container so that the quaternization treatment is reacted under the dispersant system;

[0025] The dispersant is one or more of polyethylene glycol octylphenyl ether, polyoxyethylene stearyl alcohol ether, polyvinyl alcohol and lignin, and the weight percentage of the dispersant is 2.5 wt%~20 wt%.

[0026] Optionally, during the quaternization treatment, the reagent used is an ethanolamine compound;

[0027] Wherein, the ethanolamine compound is one or more of ethanolamine, diethanolamine, triethanolamine, methylethanolamine, N-methyldiethanolamine, and N,N-dimethylethanolamine, and the weight percentage of the ethanolamine compound is 2wt%~20wt%;

[0028] During the quaternization treatment, the reaction temperature is 50°C to 90°C, and the reaction time is 6 to 24 hours.

[0029] Optionally, the weight ratio of latex balls to sulfonated balls is 1:2 to 1:10;

[0030] The agglomeration time of latex balls and sulfonated balls is 0.5~4 hours.

[0031] Optionally, in step S4, before loading the latex agglomerated ion chromatography filler into the column, the latex agglomerated ion chromatography filler is first cleaned and dried;

[0032] When packing the column, the homogenization method is used, and KOH solution is used for homogenization. After the chromatographic column is prepared, KOH solution is used for washing and testing.

[0033] Optionally, the drying temperature of the latex agglomerated ion chromatography filler is 30°C to 80°C;

[0034] The concentration of the KOH solution is 0.05~0.5mol / L;

[0035] The column packing pressure is 10~40MPa and the packing time is 0.5~3h.

[0036] By adopting the above technical scheme, the present invention provides a method for preparing a latex agglomerated anion chromatography column filler, and the goal is achieved mainly by synthesizing a monodisperse nonporous latex sphere of vinylbenzyl chloride-divinylbenzene-allyl glycidyl ether having a gradient structure from core to shell, and performing a quaternization reaction on the sphere to obtain a modified quaternized latex sphere containing β-hydroxyl. The filler obtained by the final agglomeration has improved hydrophilicity on the one hand; on the other hand, it also satisfies its use in a strong alkaline environment. The prepared hydrophilic latex agglomerated anion chromatography column filler has strong hydrophilicity and good chromatographic stability, and the broadening of seven tested anions is moderate, and the peak time is fast. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a scanning electron microscope image of styrene-divinylbenzene porous microspheres magnified 5000 times.

[0038] Figure 2 This is a scanning electron microscope image of the latex spheres synthesized in Example 1.

[0039] Figure 3 This is a scanning electron microscope image of the latex spheres synthesized in Example 7.

[0040] Figure 4 This is a scanning electron microscope image of the latex agglomerated filler synthesized in Example 1.

[0041] Figure 5 This is a chromatogram of the ion chromatography column prepared in Example 1 detecting seven anions: F-, Cl-, NO2-, Br-, NO3-, SO42-, and PO43-.

[0042] Among them, Figure 5 In the figure, the peak numbers are: 1.F - ; 2. Cl - 3. NO2 - ; 4. SO4 2- ; 5. Br - 6. NO3 - ; 7. PO4 3 . DETAILED DESCRIPTION

[0043] The present application will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant inventions, rather than to limit the inventions. It should also be noted that, for ease of description, only the parts related to the invention are shown in the accompanying drawings.

[0044] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0045] Example 1

[0046] Step (1): 1.78 g of vinylbenzyl chloride (VBC), 0.08 g of sodium dodecyl sulfate (SDS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of potassium persulfate (KPS) was added, and the mixture was reacted at 60°C for 1 h; 0.134 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 1 h; 3.58 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 7 h to obtain latex balls.

[0047] Step (2): Weigh 10 g of lignin, 5 g of diethanolamine and 35 g of latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 h, and then wash and dry.

[0048] Step (3): Weigh 1 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 5 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0049] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0050] Example 2

[0051] The difference between this embodiment and embodiment 1 is the change in the monomer ratio and the change in the dispersant.

[0052] Step (1): 1.34 g of vinylbenzyl chloride (VBC), 0.08 g of sodium dodecyl sulfate (SDS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of potassium persulfate (KPS) was added, and the mixture was reacted at 60°C for 0.5 h; 0.134 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 1 h; 4.0 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 9 h to obtain latex balls.

[0053] Step (2): Weigh 10 g PVA, 5 g diethanolamine and 35 g latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 h, and then wash and dry.

[0054] Step (3): Weigh 1 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 5 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0055] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0056] Example 3

[0057] The difference between this example and Example 2 is the change in the cross-linking agent ratio and the quaternization step.

[0058] Step (1): 1.34 g of vinylbenzyl chloride (VBC), 0.08 g of sodium dodecyl sulfate (SDS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of potassium persulfate (KPS) was added, and the mixture was reacted at 60°C for 1 h; 0.536 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 2 h; 4.0 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 9 h to obtain latex balls.

[0059] Step (2): Weigh 7.5 g of Tween 20, 10 g of diethanolamine and 32.5 g of latex balls into a three-necked flask, raise the temperature to 80°C, stir for 24 h, and then wash and dry.

[0060] Step (3): Weigh 1 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 5 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0061] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0062] Example 4

[0063] The difference between this embodiment and embodiment 2 is the change in the cross-linking agent ratio, the amination process and the agglomeration ratio.

[0064] Step (1): 1.34 g of vinylbenzyl chloride (VBC), 0.08 g of sodium dodecyl sulfate (SDS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of potassium persulfate (KPS) was added, and the mixture was reacted at 60°C for 0.5 h; 0.268 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 1 h; 4.0 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 12 h to obtain latex balls.

[0065] Step (2): Weigh 12.5 g Triton X-100, 7.5 g diethanolamine and 30 g latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 h, and then wash and dry.

[0066] Step (3): Weigh 2 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 5 g of sulfonated styrene-divinylbenzene (PS-DVB) balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0067] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0068] Example 5

[0069] The difference between this embodiment and embodiment 4 is the change in the types of initiator and emulsifier.

[0070] Step (1): 1.34 g of vinylbenzyl chloride (VBC), 0.08 g of sodium dodecylbenzene sulfonate (SDBS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of ammonium persulfate (APS) was added, and the mixture was reacted at 60°C for 1 h; 0.268 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 2 h; 4.0 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 7 h to obtain latex balls.

[0071] Step (2): Weigh 12.5 g Triton X-100, 7.5 g diethanolamine and 30 g latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 h, and then wash and dry.

[0072] Step (3): Weigh 1 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 5 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0073] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0074] Example 6

[0075] The difference between this embodiment and embodiment 4 is the change in the types of initiator and emulsifier, the ratio of monomers and the ratio of cross-linking agent.

[0076] Step (1): 2.68 g of vinylbenzyl chloride (VBC), 0.08 g of sodium dihexyl sulfosuccinate and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of ammonium persulfate (APS) was added, and the mixture was reacted at 60°C for 2 h; 0.536 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 2 h; 2.68 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 12 h to obtain latex balls.

[0077] Step (2): Weigh 12.5 g of Tween 20, 7.5 g of diethanolamine and 30 g of latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 h, and then wash and dry.

[0078] Step (3): Weigh 1 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 5 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0079] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0080] Example 7

[0081] Step (1): 1.78 g of vinylbenzyl chloride (VBC), 0.08 g of sodium dodecyl sulfate (SDS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of potassium persulfate (KPS) was added, and the mixture was reacted at 60°C for 1 h; 0.134 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 1 h; 3.56 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 7 h to obtain latex balls.

[0082] Step (2): Weigh 10 g of lignin, 15 g of diethanolamine and 25 g of latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 hours, and then wash and dry.

[0083] Step (3): Weigh 1 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 3 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0084] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0085] Example 8

[0086] Step (1): 1.78 g of vinylbenzyl chloride (VBC), 0.134 g of divinylbenzene (DVB), 0.08 g of sodium dodecyl sulfate (SDS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of potassium persulfate (KPS) was added, and the mixture was reacted at 60°C for 2 h; 0.268 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 2 h; 3.56 g of allyl glycidyl ether (AGE), 0.134 g of divinylbenzene (DVB), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 12 h to obtain latex balls.

[0087] Step (2): Weigh 10 g PVA, 15 g diethanolamine and 25 g latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 h, and then wash and dry.

[0088] Step (3): Weigh 2 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 4 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0089] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0090] Example 9

[0091] Step (1): 1.78 g of vinylbenzyl chloride (VBC), 0.134 g of divinylbenzene (DVB), 0.08 g of sodium dodecyl sulfate (SDS) and 30 mL of deoxygenated water were weighed into a three-necked flask, nitrogen was introduced at a flow rate of 5 mL / min to keep the reaction system in a nitrogen atmosphere, the mixture was stirred at 400 rpm for 10 min, 0.014 g of potassium persulfate (KPS) was added, and the mixture was reacted at 60°C for 2 h; 0.268 g of divinylbenzene (DVB) was weighed into a three-necked flask and reacted for 2 h; 3.56 g of allyl glycidyl ether (AGE), 0.06 g of sodium dodecyl sulfate (SDS) and 20 mL of deoxygenated water were weighed, emulsified at 5000 rpm for 10 min in a homogenizer, and then added into the three-necked flask, 0.008 g of potassium persulfate (KPS) was added, and the mixture was reacted for 10 h to obtain latex balls.

[0092] Step (2): Weigh 10 g PVA, 15 g diethanolamine and 25 g latex balls into a three-necked flask, raise the temperature to 65°C, stir for 18 h, and then wash and dry.

[0093] Step (3): Weigh 1 g of dried quaternized latex balls and disperse them in 40 mL of water, stirring to disperse them evenly; weigh 5 g of sulfonated styrene-divinylbenzene (PS-DVB) based balls and add them to the solution system, stirring for 1 hour, to obtain a latex agglomerated anion chromatography column filler.

[0094] Step (4): The latex agglomerated anion chromatography column filler was cleaned and dried, and loaded into the column using a homogenization method. The column tube specification was 4.0*250 mm. After loading, the column was flushed at a flow rate of 1.0 mL / min for 30 min and tested. The chromatograph model was IC6600 produced by Wanyi, equipped with a suppressed conductivity detector, and the test conditions were 1.0 mL / min, 15 mM kOH.

[0095] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

[0096] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A method for preparing a latex agglomerated ion chromatography column, characterized in that: The following steps are included: S1, synthetic latex ball; S2, quaternizing the synthesized latex balls; S3, agglomerating the quaternized latex balls with the sulfonated balls to obtain a latex agglomerated ion chromatography filler; S4, loading the obtained latex agglomerated ion chromatography filler into a column and testing it; Wherein, in step S1, the step of synthesizing latex balls is: S11, adding vinylbenzyl chloride monomer, emulsifier and initiator into a container, and forming latex balls with a core structure by emulsion polymerization; S12, adding a cross-linking agent into the container to react, so that the nuclear structure of the latex ball is amplified; S13, adding pre-emulsified allyl glycidyl ether and an initiator into a container to obtain monodisperse nonporous latex spheres having a core-shell structure of vinylbenzyl chloride-divinylbenzene-allyl glycidyl ether.

2. The method for preparing a latex agglomerated ion chromatography column according to claim 1, characterized in that: In step S3, the step of obtaining the latex agglomerated ion chromatography filler is as follows: S31, taking styrene-divinylbenzene porous microspheres and sulfonating them to make the styrene-divinylbenzene porous microspheres positively charged to obtain sulfonated microspheres; S32, electrostatically agglomerating the quaternized latex balls with the sulfonated balls to obtain a latex agglomerated ion chromatography column filler.

3. The method for preparing a latex agglomerated ion chromatography column according to claim 1, characterized in that: In step S11, the reaction temperature of the emulsion polymerization is 50-90°C, and the reaction time is 0.5-4 hours; The initiator is one or more of azobisisobutylamidine hydrochloride, potassium persulfate, and ammonium persulfate, and the weight percentage of the initiator is 0.05 wt% to 2 wt%; The emulsifier is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium dihexyl sulfosuccinate, and the weight percentage of the emulsifier is 1wt% to 3wt%.

4. The method for preparing a latex agglomerated ion chromatography column according to claim 1, characterized in that: In step S12, the cross-linking agent is divinylbenzene, and the weight percentage of the cross-linking agent is 2.5wt%~12.5wt%; The reaction time of the cross-linking agent is 0.5 to 4 hours.

5. The method for preparing a latex agglomerated ion chromatography column according to claim 1, characterized in that: In step S13, the weight percentage of the allyl glycidyl ether is 60wt%-80wt%.

6. The method for preparing a latex agglomerated ion chromatography column according to claim 1, characterized in that: In step S2, when the latex balls are quaternized, a dispersant is added into the container so that the quaternization treatment is reacted under the dispersant system; The dispersant is one or more of polyethylene glycol octylphenyl ether, polyoxyethylene stearyl alcohol ether, polyvinyl alcohol and lignin, and the weight percentage of the dispersant is 2.5 wt%~20 wt%.

7. The method for preparing a latex agglomerated ion chromatography column according to claim 6, characterized in that: In the quaternization treatment, the reagent used is an ethanolamine compound; Wherein, the ethanolamine compound is one or more of ethanolamine, diethanolamine, triethanolamine, methylethanolamine, N-methyldiethanolamine, and N,N-dimethylethanolamine, and the weight percentage of the ethanolamine compound is 2wt%~20wt%; During the quaternization treatment, the reaction temperature is 50°C to 90°C, and the reaction time is 6 to 24 hours.

8. The method for preparing a latex agglomerated ion chromatography column according to claim 1, characterized in that: In step S3, the weight ratio of the latex balls to the sulfonated balls is 1:2 to 1:10; The agglomeration time of latex balls and sulfonated balls is 0.5~4 hours.

9. The method for preparing a latex agglomerated ion chromatography column according to claim 1, characterized in that: In step S4, before loading the latex agglomerated ion chromatography filler into a column, the latex agglomerated ion chromatography filler is first cleaned and dried; When packing the column, the homogenization method is used, and KOH solution is used for homogenization. After the chromatographic column is prepared, KOH solution is used for washing and testing.

10. The method for preparing a latex agglomerated ion chromatography column according to claim 9, characterized in that: The drying temperature of latex agglomerated ion chromatography filler is 30℃~80℃; The concentration of the KOH solution is 0.05~0.5mol / L; The column packing pressure is 10~40MPa and the packing time is 0.5~3h.